Midpalatal suture: evaluation of the morphological maturation stages via bone density - Dani Abo Samra; Rania Hadad (Progress in Orthodontics, 2018)
Abstract Background To investigate the relationship between the morphological maturation stages of the midpalatal suture and its bone densities. Methods The sample consisted of 91 subjects aged 8–18 years who underwent cone beam computed tomography. All images were examined to classify morphological maturation of the midpalatal suture to five groups according to Angelieri et al. Bone density of the midpalatal suture was measured at the maxillary and palatal regions. Kruskal-Wallis and Mann-Whitney U tests were used to analyze the difference between groups. Results Bone density of the midpalatal suture was significantly higher in the palatal region in E stage and in the maxillary region in D and E stages. Conclusions It is concluded that the change in bone density of the midpalatal suture between the morphological maturation stages supports their reliability in clinical application.